Factorization for energy-energy correlator in heavy ion collision - Balbeer Singh; Varun Vaidya (Journal of High Energy Physics)
Abstract We present a factorization formula for the energy-energy correlator in the collinear limit for the case of heavy ion collisions. Employing Soft Collinear Effective Theory, we provide a complete framework for jet production and evolution by separating the jet dynamics from the universal medium physics to all orders in perturbation theory in terms of gauge invariant operators. The EFT allows us to precisely define the domain of validity of different approximations and to systematically go beyond leading order results in the literature through radiative corrections. For this observable, we show where the leading order GLV and BDMPS-Z results are valid and infer that higher order radiative corrections lead to both DGLAP and BFKL evolutions. We further show the impact of BFKL resummation on the medium induced jet function for two point energy correlator. Crucially, the EFT approach enables us to evaluate the universality of the non-perturbative physics which is the key to predictive power in a strongly coupled medium.